Resolving Transcriptional States and Predicting Lineages in the Annelid Capitella teleta Using Single-Cell RNAseq - Sur, Abhinav; Meyer, Néva P. (Frontiers in Ecology and Evolution, 2021)
Evolution and diversification of cell types has contributed to animal evolution. However, gene regulatory mechanisms underlying cell fate acquisition during development remains largely uncharacterized in spiralians. Here we use a whole-organism, single-cell transcriptomic approach to map larval cell types in the annelid Capitella teleta at 24- and 48-hours post gastrulation (stages 4 and 5). We identified eight unique cell clusters (undifferentiated precursors, ectoderm, muscle, ciliary-band, gut, neurons, neurosecretory cells and protonephridia), thus helping to identify previously uncharacterized molecular signatures such as novel neurosecretory cell markers. Analysis of coregulatory programs in individual clusters revealed gene interactions that can be used for comparisons of cell types across taxa. We examined the neural and neurosecretory clusters more deeply and characterized a differentiation trajectory starting from dividing precursors to neurons using Monocle3 and velocyto. Pseudotime analysis along this trajectory identified temporally-distinct cell states undergoing progressive gene expression changes over time. Our data revealed two potentially distinct neural differentiation trajectories including an early trajectory for brain neurosecretory cells. This work provides a valuable resource for future functional investigations to better understanding neurogenesis and the transitions from neural precursors to neurons in an annelid.